Close-coupling calculations of 64.6 eV e-He ionization - Bray, Igor; Fursa, Dmitry; Kadyrov, Alisher; Stelbovics, Andris; Colgan, J.; Pindzola, M. (IOP, 2011)
The convergent close-coupling and the time-dependent close-coupling methods are applied to the calculation of 64.6 eV electron-impact ionization of the ground state of helium resulting in two 20 eV outgoing electrons. The results of the calculations are compared with measured fully differential cross sections in various geometries. For the generally large in-plane geometries there is good agreement between the two theories and experiment. For the out-of-plane case the cross sections are generally smaller and some differences between the two calculations are evident, as well as experiment.